Risks and Opportunities of Reforms Putting Primary Care in the Driver's Seat; Comment on "Governance, Government, and the Search for New Provider Models" - Monica Andersson Bäck (Kerman University of Medical Sciences, 2016)
Recognizing the advantages of primary care as a means of improving the entire health system, this text comments on reforms of publicly funded primary health centers, and the rapid development of private forprofit providers in Sweden. Many goals and expectations are connected to such reforms, which equally require critical analyses of scarce resources, professional trust/motivation and business logic in the wake of freedom and control of ownership and management. In line with Saltman and Duran, this article calls for research and a methodologically developed approach to capture everyday practice in-depth and how regulation, market incentives and patient demands are met by professionals and primary care leaders.